Ekositem Perairan Payau Hutan Mangrove Teluk Belukar Kecamatan Gunungsitoli Utara - Waruwu, Julpin carles; Harefa, Meserius (Jurnal Perikanan dan Kelautan, 2025)
The brackish water ecosystem in the mangrove forest of Teluk Belukar, North Gunungsitoli District, is a coastal area with high biodiversity and significant ecological functions. This study aims to identify the ecological condition of the brackish water ecosystem, the biodiversity it supports, and its role in the surrounding environment. Observations were conducted through field surveys, identification of flora and fauna species, and analysis of water quality based on physical and chemical parameters. The results show that the area is dominated by mangrove species such as Rhizophora mucronata, Avicennia marina, and Sonneratia alba, and serves as a vital habitat for various species of fish, mollusks, and crustaceans. Water salinity ranged from 10 to 20 ppt, indicating a stable brackish water environment.